Research progress of mimic multi-execution scheduling algorithm - Zhengbin ZHU; Qinrang LIU; Dongpei LIU; Chong WANG (Tongxin xuebao)
Mimic defense is the new active defense technology based on the dynamic heterogeneous redundant architecture.With inherent uncertainty, heterogeneous, redundant and negative feedback features, it can significantly improve the robustness and security of system.Among them, the scheduling algorithm is the key to mimic defense technology, which advantages and disadvantages directly affect the ability of system to resist attacks based on known or unknown vulnerabilities.Based on this, the principle and goal of mimic scheduling algorithm were firstly introduced.Then the state-of-the-art of mimic scheduling algorithms were analyzed and summarized from three aspects, such as scheduling object, scheduling quantity and scheduling timing.Finally, the future research direction and trend of mimic scheduling algorithms were prospected.